The effect of customer value and trust on customer satisfaction and its impact on customer loyalty - Yudhi Koesworodjati; Ratu Hedy Syahidah Budiarti (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Customer value and trust are important factors that can significantly impact customer satisfaction. When a customer perceives that they are receiving value from a product or service and trust the brand or business that is providing it, they are more likely to be satisfied with their overall experience. This study aims to determine the Influence of Customer Value and Trust on Customer Satisfaction and its impact on the Costumer Loyalty Survey on the Costumer Spare Parts Excavator in CV. Bandung Jaya Diesel Bandung. This research was conducted by taking a sample of 70 people. Analysis of the results of this study using path analysis. The results of this research are the influence of the variable (Y) consumer satisfaction on consumer loyalty is indicated by a regression coefficient of 0.867 with other factors other than the variable (Z) customer loyalty of 0.133. Thus, it can be concluded that there is an influence of consumer satisfaction (Y) on consumer loyalty (Z) of 86.7% and other factors that affect consumer loyalty other than customer satisfaction (Y) of 13.3%.